2012
DOI: 10.1093/cercor/bhs187
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Organization of Structural Brain Networks

Abstract: Recent findings from developmental neuroimaging studies suggest that the enhancement of cognitive processes during development may be the result of a fine-tuning of the structural and functional organization of brain with maturation. However, the details regarding the developmental trajectory of large-scale structural brain networks are not yet understood. Here, we used graph theory to examine developmental changes in the organization of structural brain networks in 203 normally growing children and adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
188
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(213 citation statements)
references
References 88 publications
(141 reference statements)
22
188
3
Order By: Relevance
“…One might expect, for example, that over the course of human development, periods during which cognitive capability is enhanced and Hebbian processes are particularly active may also correspond to increased salience of rich-club structures. This idea is supported by preliminary evidence from developmental neuroimaging studies which have revealed an increase in the number and importance of connector hubs in normally growing children and adolescents [45].…”
Section: Discussionmentioning
confidence: 74%
“…One might expect, for example, that over the course of human development, periods during which cognitive capability is enhanced and Hebbian processes are particularly active may also correspond to increased salience of rich-club structures. This idea is supported by preliminary evidence from developmental neuroimaging studies which have revealed an increase in the number and importance of connector hubs in normally growing children and adolescents [45].…”
Section: Discussionmentioning
confidence: 74%
“…Acquisition of 1.5 T MRI data was collected according to a standardized protocol (Jack et al, 2008). The scanning protocol included a high- resolution T1-weighted, rapid gradient echo (MP-RAGE) sequence.…”
Section: Adni Participants and Mri Acquisitionmentioning
confidence: 99%
“…This network is characterized by high intrinsic functional connectivity between posterior cingulate cortex (PCC), medial prefrontal cortex, inferior parietal lobule, and lateral and medial temporal lobes (Buckner et al, 2008). The functional integrity of the default network is reduced in older adults (Hafkemeijer et al, 2012), with further reductions in Alzheimer's disease (AD) (Greicius et al, 2004;Damoiseaux et al, 2012;Hafkemeijer et al, 2012;Sheline and Raichle, 2013). Functional connectivity within the default network differs in APOE 4 allele carriers, a risk factor for late-life pathological changes (Filippini et al, 2009;Sheline et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, while global brain volume is largely genetically deter mined, regional brain volumes, and therefore structural co variance measurements, are more flexibly determined by a number of factors. 3,4 Such factors range from genetic 5 and other developmental influences [6][7][8] to aging effects. 9,10 Other aspects related to the basic principles of brain organ ization, such as the existence of functional connectivity, or cor related spontaneous activity across time between distant struc tures, may also influence the patterns of structural covariance.…”
Section: Introductionmentioning
confidence: 99%